Microalgae-based biofertilizers improve fertility and microbial community structures in the soil of potted tomato - Song, Xiaotong; Liu, Jiayi; Feng, Yanzhang; Zhou, Chengxu; Li, Xiaohui; Yan, Xiaojun; Ruan, Roger; Cheng, Pengfei (Frontiers in Plant Science, 2024)
Continuous crop cropping would decrease soil nutrients and destroy microbial community structure, and the development of eco-friendly and effective biofertilizers is necessary at present conditions. In this study, the preserving microalgal strain Tribonema sp. (H) was firstly selected to be combined with agroforestry waste (shell powder, straw fermentation liquid) and agroforestry microorganism Bacillus sp. to form microalgae-based fertilizers in continuous cropping soil of potted tomato. Compared to the control (CK), microalgae-based fertilizers (concentration: 4.45 × 10 6 cells/ml, dosage: 20 ml/day) could improve soil nutrients and salinization indicators. Specifically, the combination of Tribonema sp. and shell powder (HB) could reduce electrical conductivity (EC) by 33.7% and significantly increase the Ca 2+ content by 59.4%; Tribonema sp. and Bacillus sp. (HY) could improve the effects of available phosphorous (AP), DOC, DON, NH4 + -N, NO3 --N, Mg 2+ in the soil by 27.4%, 231.3%, 403.4%, 125.2%, 215.6%, 73.4%, respectively. Microalgae-based fertilizers alter the abundance of soil bacteria and fungi, causing beneficial bacteria such as Thermonaerobaculia, Subgroup_10, Sordariomycetes, and Microascaceae to increase, while pathogenic bacteria like Pseudomonas, Togniniaceae, and Phaeoacremonium decreased. Combining microalgae with agroforestry wastes as the biofertilizer is promising to improve the microbial community structure of the soil with continuous cropping, which will aid in the increasement of tomato production and promote green agricultural development.